Will Serious Shortage Protocols help ease drug shortages?. Issue 5 (21st May 2020) - Dowden, Angela
Abstract : Historically, pharmacists have had very limited options when faced with drugs that are out of stock, but recently introduced Serious Shortage Protocols could theoretically help mitigate shortages by giving them the power to dispense something different. But what do pharmacists and prescribers make of these new protocols, and what are the implications for patients?